Addition of V2O5 and V2O3 to the CaO–FeO–Fe2O3–MgO–SiO2 database for vanadium distribution and viscosity calculations. (September 2021) - Jantzen, Tatjana; Yazhenskikh, Elena; Hack, Klaus; Baben, Moritz to; Wu, Guixuan; Müller, Michael
Abstract: Vanadium oxides were added to the existing GTOx database because of its important role in the ferro-titanium metallurgy as well as in petroleum coke gasification. The CaO–FeO–Fe2 O3 –MgO–SiO2 system is a part of GTOx database and is chosen because of the existence of experimentally determined vanadium distributions between vanadium ferroalloys and metallurgical slags. The CaO–FeO–Fe2 O3 –MgO–SiO2 –V2 O3 –V2 O5 system including all binary and ternary sub-systems was thermodynamically assessed using all available experimental data. Vanadium was introduced into the thermodynamic description of solid solution phases such as MeO, Spinel, Corundum and Ca2 SiO4 -α using available experimental information. Particular attention was given to the phase Spinel which forms the wide completely miscible solid solution Fe3 O4 –FeV2 O4 –MgV2 O4 –MgFe2 O4 . The thermodynamic description of the metallic vanadium containing systems was taken from the SGTE alloy database. With the knowledge about the complex behavior of vanadium in slags as well as in liquid metal alloys it is possible to calculate the vanadium distribution ratios (V)/[V] between iron melts and slags in a wide range of temperatures and compositions, corroborating the validity of the model under reducing conditions. The additionally developed viscosity model shows good agreement between the calculated and experimental values in vanadium-containing slags.